Kebijakan Pariwisata Lombok untuk Melepaskan Ketergantungan Terhadap Pariwisata Bali Menuju Pariwisata Internasional - Lalu Puttrawandi Karjaya; Mala Mardialina; Alfian Hidayat (Department of International Relations, Brawijaya University, 2016)
It was not just Bali who received negative effects of the Bali bombing I and II. effect that two incident was also felt by the tourism industry in Lombok. long-term goal of this research is, (1) Assist the Government of measuring the level of dependence Against Bali Lombok tourism; (2) Assist the Government to see how effective ongoing policy to break away from dependence; and (3) Assist the government to see the impact of these policies on the industries that have been supporting the tourism sector. While specific targets to be achieved, namely, (1) To see howdependent Lombok to Bali in the field of tourism; (2) To analyze and draft policies that can effectively release the dependence on promoting tourism in Bali and Lombok tourism sector. The method used for this study, (1) Observation; Researchers observed by jumping directly to the agencies that participate in the creation and implementation of tourism policy to obtain preliminary data research, (2) Interview, direct interviews with stakeholders such as the Governor, the Regent , head of tourism and planning staff as well as those players in the industry that supports the tourism sector to see the impact and the effectiveness of the policies, and ( 3 ) phases of the project. Additionally held Research Library, of the problems that have been identified in the literature relating done, to support and understand the basic concepts underlying and can resolve issues being examined. This literature study was obtained from reference books, magazines, articles, information from the internet, as well as other literature related to the problem being researched.Keywords: Dependency, Terorism, Tourism Policy